Effect of Liquid Organic Fertilizer Type and Concentration on the Growth and Production of Purple Eggplant (Solanum melongena L.) - Agus Sulistyono; Kiki Adelia Putri; Djarwatiningsih Pongki S. (The University of Lampung, 2023)
The productivity of purple eggplant has decreased and consumption continues to increase, it is necessary to increase the productivity of purple eggplant. Increasing productivity can be done by applying liquid organic fertilizer (LOF) derived from organic waste such as banana peels and fish waste. The purpose of this study was to determine the type and concentration of LOF that can help the growth and yield of purple eggplant. This research was conducted on the land of the Faculty of Agriculture, University of National Development (UPN)